The comparative mechanistic aspects of Trichoderma and Probiotics: Scope for future research. (December 2017) - Sharma, Vivek; Salwan, Richa; Sharma, P.N.
Abstract: Probiotics and biocontrol agents are used increasingly due to their health benefits to human and agricultural crops in combating various pathogenic diseases and other metabolic disorders. Probiotics are known to impart several health benefits to human. Similar to probiotics strains, the biocontrol agents such as Trichoderma offer several advantages to their associated host plants which are helpful in combating both biotics and abiotic conditions under adverse conditions. A wide repertoire of biologically active metabolites is deployed by Trichoderma species for pathogen's exclusion including competition for space, nutrients and production of antimicrobial compounds. Also, the strains of Trichoderma strains are capable of modulating growth promotion, enhanced uptake of nutrients and immune responses of the host plant through adaptive reprogramming of its own as well as host transcriptome. Although molecular arsenal of Trichoderma and probiotics differs in their structural organization starting from initial epithelial adherence or root colonization to final benefits to their associated hosts under various environmental conditions. Still both of them shares unique similarity in their mechanism of actions either directly by discouraging the pathogens or by boosting the responses of the associated host. Therefore this review is focused on biocontrol and probiotics mechanisms and highlighting Trichoderma as plant probiotics due to its multidimensional beneficial aspects. Highlights: The present review articles highlights the basic similarity between biocontrol agent Trichoderma and microbes used as probiotics. The review also discusses the scope of future improvement in both microbes. Both microbes provides a plethora of benefits to their associated host during abiotic and biotic stress responses.